Social Actor Representation in Joe Biden’s Speech about the End of Afghan War (A Critical Discourse Analysis) - Floranti, Astri Dwi; Gunawan, Wawan; Mubarok, Yasir (Journal of Languages and Language Teaching, 2024)
On August 31, 2021, Joe Biden announced officially the drawdown of the United States military forces from Afghanistan war indicating the end of the longest war in American history for 20 years. This study posits that Biden's speech serves as a means of political engagement not only as the announcement of a decision but also as the cultivation of a shared perspective and consciousness on the role and position of the United States and its allies in the Afghanistan war. This study aims at examining the representation of social actors in his speech using van Leeuwen's approach of critical discourse analysis (van Leeuwen, 2008). This study investigates the ways how the social actors are depicted in the speech and uncovers the underlying ideology behind their portrayal. According to the result, the dominance of inclusion strategies (84.1%) indicates various ways of portrayal the social actors either. The recontextualization of the Afghanistan war in the speech is constructed significantly by beliefs and attitudes of social actors within US sides. The speech expresses the role of the current president, US forces and government aiming at the shape of public opinion positively for the future of Americans and the latest national interest of United States Furthermore, this speech emphasizes the American foreign policy during Biden's administration about the multilateralism. Its implementation is proposing the diplomacy, specifically using non-military means to protect the human rights and build strong international collaboration. Biden's decision to end the Afghan war is a deliberate attempt to promote peace and stability in the United States by focusing on its future rather than dwelling on the past.